Recurring and Adaptable Binding Motifs in Broadly Neutralizing Antibodies to Influenza Virus Are Encoded on the D3-9 Segment of the Ig Gene - Wu, Nicholas C.; Yamayoshi, Seiya; Ito, Mutsumi; Uraki, Ryuta; Kawaoka, Yoshihiro; Wilson, Ian A. (Cell host & microbe, 2018)
Discovery and characterization of broadly neutralizing antibodies (bnAbs) to the influenza hemagglutinin (HA) stem have provided insights for the development of a universal flu vaccine. Identification of signature features common to bnAbs from different individuals will be key to guiding immunogen design. S9-3-37 is a bnAb isolated from a healthy H5N1 vaccinee. Here, structural characterization reveals that the D3-9 gene segment of S9-3-37 contributes most of the interaction surface with the highly conserved stem epitope on HA. Comparison with other influenza bnAb crystal structures indicates that the D3-9 segment provides a general mechanism for targeting HA stem. Interestingly, such bnAbs can approach the HA stem with vastly different angles and orientations. Moreover, D3-9 can be translated in different reading frames in different bnAbs yet still target the same HA stem pocket. Thus, the D3-9 gene segment in the human immune repertoire can provide a robust defense against influenza virus. [Display omitted] •Structure of bnAb S9-3-37 bound to influenza hemagglutinin stem was determined•D3-9-encoded region of S9-3-37 contributes majority of the interaction surface with HA•D3-9 gene segment of S9-3-37 can engage the HA stem in two different reading frames•D3-9 gene segment represents a recurring mechanism for antibody targeting of HA stem Identifying signature features common to broadly neutralizing antibodies (bnAbs) is key to universal flu vaccine design. Wu et al. report that the D3-9 encoded segment of an influenza hemagglutinin stem-targeting bnAb contributes the majority of the interaction surface and is a recurring motif in antibodies that target the hemagglutinin stem.